Prevalence of Dissociative Convulsions in Patients with Dissociative Disorder in a Tertiary Care Hospital: A Descriptive Cross-sectional Study - Khattri, Jai Bahadur (JNMA J Nepal Med Assoc, 2019)
INTRODUCTION: Dissociative disorder is one of the common psychiatric problems encountered very frequently in the hospital setting. The aim of the study is to find out the prevalence of dissociative convulsions type in patients suffering from dissociative disorder attending Psychiatry outpatient department of a tertiary care hospital. METHODS: The descriptive cross-sectional study was carried out in a tertiary care hospital from February 2019 to July 2019 after taking ethical approval (MEMG/IRC/210/GA). The patients attending Psychiatry outpatient department of Manipal Teaching Hospital, Pokhara, Nepal were included in the study. The diagnosis of dissociative convulsion and other types of dissociative disorder was done according to the International Classification of Disease–10 Classification of Mental and Behavioural Disorders - Diagnostic Criteria for Research. Statistical Package for Social Sciences version 22 was used for the analysis of the data and point estimate at 95% Confidence interval was calculated along with frequency and proportion for binary data and the analysis was done. RESULTS: Sixty six patients were included in the study. The prevalence of dissociative convulsion was 86.3% in the present study, at 95% Confidence interval, (78-94.6%). Five patients (7.6%) were found to be suffering from dissociative motor disorders and 4 (6.1%) patients were suffering from trance and possession disorder. CONCLUSIONS: The prevalence of dissociative convulsion type is high in patients suffering from dissociative disorder in the Nepalese context. Future studies should be conducted to understand this disorder and to propose therapeutic guidelines.